Tilted pillar array fabrication by the combination of proton beam writing and soft lithography for microfluidic cell capture Part 2: Image sequence analysis based evaluation and biological application. Issue 3 (21st August 2017) - Járvás, Gábor; Varga, Tamás; Szigeti, Márton; Hajba, László; Fürjes, Péter; Rajta, István; Guttman, András
Abstract: As a continuation of our previously published work, this paper presents a detailed evaluation of a microfabricated cell capture device utilizing a doubly tilted micropillar array. The device was fabricated using a novel hybrid technology based on the combination of proton beam writing and conventional lithography techniques. Tilted pillars offer unique flow characteristics and support enhanced fluidic interaction for improved immunoaffinity based cell capture. The performance of the microdevice was evaluated by an image sequence analysis based in‐house developed single‐cell tracking system. Individual cell tracking allowed in‐depth analysis of the cell–chip surface interaction mechanism from hydrodynamic point of view. Simulation results were validated by using the hybrid device and the optimized surface functionalization procedure. Finally, the cell capture capability of this new generation microdevice was demonstrated by efficiently arresting cells from a HT29 cell‐line suspension.